Permainan Tradisional Batak Toba sebagai Ide Penciptaan Lukisan Menggunakan Media Kulit Kuda - Henri Joko Lumban Gaol; Nelson Tarigan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
The creation of this artwork was inspired by the artist, who is a native of the Batak Toba tribe from Pollung District, Humbang Hasundutan Regency. This area is known as a horse breeding region, which produces waste in the form of horsehide scraps. This waste is then utilized as an alternative medium for painting. The idea for the artwork was inspired by traditional Batak Toba games rich in cultural value. This research aims to visualize the form, historical background, and function of traditional Batak Toba games through paintings. In the creation process, horsehide and oil paint were used as media. Each painting depicts the visual form of the traditional game with a simple approach yet still reflects the characteristics and meaning of the games. The method of creating the artwork is based on the stages described by Hedriyana, which include five stages: preparation, elaboration, contemplation, the creation process, and completion of the artwork. The final result of this research is a series of paintings with various titles, as the author's visual interpretation of traditional Batak Toba games.